Cognitive analytical tools for cost management of innovation activity - Svitlana Labunska (Problems and Perspectives in Management, 2019)
Promotion of innovations on the market is hampered in Ukraine by the lack of methodological approaches for analyzing the efficiency of innovative projects. The lack of appropriate methodology leads companies to refuse to innovate because of the uncertainty of final economic outcomes. The introduction of project based methods for innovation activity management allows, on the one hand, to reconcile strategic and operational objectives within the innovation process, innovation activity and general financial and economic activity of the enterprise, and on the other hand, to implement cognitive approaches to organization of company’s innovation management.The research argues the possibilities of applying the canonical correlation method for structuring the causal links between the determined components of a company innovative capability, such as innovation potential, innovative business opportunities and system margin. As these components may be further assessed by quantitative indices, the method of regression analysis is also used to develop analytical tools for innovation management, which allow to reveal the interrelated impact of expenses on the results of innovation activity. The paper analyzes changes in a company innovative capability that can be provoked by increased material, depreciation, labor and information costs and discusses directions of interrelated changes. Practical testing of submitted proposals is realized based on the Ukrainian companies’ statements for 2012–2017.